Stable Isotopes and Zooarchaeology at Teotihuacan, Mexico Reveal Earliest Evidence of Wild Carnivore Management in Mesoamerica. - Nawa Sugiyama; Andrew D Somerville; Margaret J Schoeninger (PLoS ONE, 2015)
From Roman gladiatorial combat to Egyptian animal mummies, the capture and manipulation of carnivores was instrumental in helping to shape social hierarchies throughout the ancient world. This paper investigates the historical inflection point when humans began to control animals not only as alimental resources but as ritual symbols and social actors in the New World. At Teotihuacan (A.D. 1-550), one of the largest pre-Hispanic cities, animal remains were integral components of ritual caches expressing state ideology and militarism during the construction of the Moon and the Sun Pyramids. The caches contain the remains of nearly 200 carnivorous animals, human sacrificial victims and other symbolic artifacts. This paper argues the presence of skeletal pathologies of infectious disease and injuries manifest on the carnivore remains show direct evidence of captivity. Stable isotope analysis (δ13C and δ15N) of bones and teeth confirms that some of these carnivores were consuming high levels of C4 foods, likely reflecting a maize-based anthropocentric food chain. These results push back the antiquity of keeping captive carnivores for ritualistic purposes nearly 1000 years before the Spanish conquistadors described Moctezuma's zoo at the Aztec capital. Mirroring these documents the results indicate a select group of carnivores at Teotihuacan may have been fed maize-eating omnivores, such as dogs and humans. Unlike historical records, the present study provides the earliest and direct archaeological evidence for this practice in Mesoamerica. It also represents the first systematic isotopic exploration of a population of archaeological eagles (n = 24) and felids (n = 29).